Fatty acid oxidation in immune function - Kemp, Felicia; Braverman, Erica L.; Byersdorfer, Craig A. (Frontiers in Immunology, 2024)
Cellular metabolism is a crucial determinant of immune cell fate and function. Extensive studies have demonstrated that metabolic decisions influence immune cell activation, differentiation, and cellular capacity, in the process impacting an organism's ability to stave off infection or recover from injury. Conversely, metabolic dysregulation can contribute to the severity of multiple disease conditions including autoimmunity, alloimmunity, and cancer. Emerging data also demonstrate that metabolic cues and profiles can influence the success or failure of adoptive cellular therapies. Importantly, immunometabolism is not one size fits all; and different immune cell types, and even subdivisions within distinct cell subtypes, utilize different metabolic pathways to optimize function. Metabolic preference can also change depending on the microenvironment in which cells are activated. For this reason, understanding the metabolic requirements of different subsets of immune cells is critical to therapeutically modulating different disease states or maximizing cellular function for downstream applications. Fatty acid oxidation (FAO), in particular, plays multiple roles in immune cells, providing both pro- and anti-inflammatory effects. Herein, we review the major metabolic pathways available to immune cells, then focus more closely on the role of FAO in different immune subsets. In turn, understanding how and why FAO is utilized by different immune cells will allow for the optimal design of therapeutic interventions targeting this pathway.